2019
DOI: 10.1016/j.sxmr.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The History of Estrogen Therapy

Abstract: Introduction: Menopausal hormone therapy (MHT) has proven an effective treatment for the amelioration of symptoms of menopause. The idea that a substance was the missing factor in a woman's body after menopause dates to the 1800's when cow ovarian tissue was injected into German women in a successful attempt to reverse the sexual symptoms of menopause. The early 1900's saw the rise of commercialized menopause "treatments" that ranged in substance, and even theoretical, efficacy. The role of estrogen was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
0
19
0
3
Order By: Relevance
“…This is of considerable importance to clinical management of women’s health. For example, the oral, nonsteroidal aromatase inhibitor letrozole, employed in the current NHP study, is widely used in clinical practice, including minimizing recurrence of estrogen receptor positive breast cancer following surgical intervention [ 105 , 106 ] and enabling menopausal hormone therapy [ 107 , 108 ]. Not surprisingly, such long-term aromatase inhibition can exert a highly negative effect on female sexuality, engaging personally distressing sexual dysfunction, vaginal atrophy, and dyspareunia [ 42 , 106 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is of considerable importance to clinical management of women’s health. For example, the oral, nonsteroidal aromatase inhibitor letrozole, employed in the current NHP study, is widely used in clinical practice, including minimizing recurrence of estrogen receptor positive breast cancer following surgical intervention [ 105 , 106 ] and enabling menopausal hormone therapy [ 107 , 108 ]. Not surprisingly, such long-term aromatase inhibition can exert a highly negative effect on female sexuality, engaging personally distressing sexual dysfunction, vaginal atrophy, and dyspareunia [ 42 , 106 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions for the prevention and management of HFpEF in postmenopausal women has solely been the use of menopausal hormonal treatment until the findings of the Women's Health Initiative randomized controlled trial and others, reporting the side effects and discouraged their usage significantly (Rossouw et al, 2002;Modena et al, 2005;Schierbeck et al, 2012;Antoine et al, 2016;Iorga et al, 2017;Kohn et al, 2019). Exploration of the mechanisms causing the reported side effects revealed that the late initiation of menopausal hormonal treatment and the usage of the combination of conjugated equine estrogen with medroxyprogesterone acetate as the probable causes (LaCroix et al, 2011;Maria Grazia, 2016;Hickey et al, 2018;Shufelt et al, 2018).…”
Section: Prospects On Therapeutic Interventions For Heart Failure With Preserved Ejection Fraction Managementmentioning
confidence: 99%
“…Moreover, the dose and duration of ET remain conservative owing to an increased risk of heart disease, stroke, and breast cancer. 19 Numerous studies have shown that estrogen regulates cellular proliferation, differentiation, and keratinization of the gingival epithelium. [20][21][22] Phytoestrogens, especially soy isoflavones (SI), are associated with a low risk of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Although estrogen supplementation is highly effective in preventing PMO and also Food and Drug Administration (FDA)‐approved, the effect of ET on periodontitis still needs to be studied. Moreover, the dose and duration of ET remain conservative owing to an increased risk of heart disease, stroke, and breast cancer 19 . Numerous studies have shown that estrogen regulates cellular proliferation, differentiation, and keratinization of the gingival epithelium 20–22 .…”
Section: Introductionmentioning
confidence: 99%